Finite Element Analysis of Stress Distribution in Monolithic High-Translucency Zirconia Dental Prostheses - Fernando Araújo da Costa Ward; Luciano Pessanha Moreira; Pedro Araújo da Costa Ward; Paula Cipriano da Silva; Manuel Fellipe Rodrigues Pais Alves; Claudinei Santos (Oral)
Background/Objectives: High-translucency zirconia is a dental ceramic offering excellent aesthetic results but with mechanical limitations restricting its applications. This study aimed to simulate the mechanical behavior of anatomical dental prostheses made from high-translucency zirconia using the finite element method (FEM) to assess the material’s reliability. Methods: Samples of high-translucency zirconia were compacted, sintered, and characterized for relative density. Structural and microstructural analyses were performed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). Its mechanical properties, including hardness, fracture toughness, and flexural strength, were measured. Additionally, elastic parameters such as Young’s modulus and Poisson’s ratio were determined using the impulse excitation technique and subsequently employed in numerical simulations under various masticatory loads (50 to 500 N). These simulations modeled an anatomical molar (tooth 26) using the HyperMesh and ABAQUS codes, applying loads from three directions: vertical, angular (45°), and horizontal, at different points on the prosthesis. Results: The sintered zirconia ceramics exhibited excellent densification and a microstructure composed of cubic and tetragonal grains (c-ZrO2 and t-ZrO2). The measured properties included a hardness of 1315 ± 48 HV, fracture toughness of 3.7 ± 0.2 MPam1/2, and flexural strength of 434 ± 67 MPa. Elastic parameters were determined as a Young’s modulus of 192.2 ± 4.8 GPa and a Poisson’s ratio of 0.31. Numerical simulations demonstrated that vertically applied loads of 500 N resulted in a maximum stress of approximately 299.2 MPa, horizontal stress reached 320.8 MPa at a 200 N load, and angular stress peaked at 447.3 MPa under a 350 N load. These findings indicate that the material can safely withstand these conditions without failure. Conclusions: Within the limits of this investigation, the methodology proved to be an effective tool for predicting the mechanical behavior of new dental ceramics. For high-translucency zirconia, the material demonstrated high reliability under masticatory vertical loads up to 500 N, angular loads up to 350 N, and horizontal loads up to 200 N.